Health Behaviors and Associated Feelings of Remote Workers During the COVID-19 Pandemic-Silesia (Poland) - Agnieszka Białek-Dratwa; Elżbieta Szczepańska; Mateusz Grajek; Beata Całyniuk; Wiktoria Staśkiewicz (Frontiers Media S.A., 2022)
During the COVID pandemic in Poland, lockdown and remote work affected a very large segment of the population. This situation has many negative consequences both in terms of health and also emotionally. In our study, we focused on eating behaviors as well as health behaviors such as alcohol consumption, smoking, physical activity while working remotely, but also the emotions that occur while being at home working for long periods of time and how these emotions affect diet, eating behaviors and overall well-being using the standardized WHO-5 and TFEQ13 questionnaires. Surveys completed by 225 individuals doing remote work from home or hybrid work. During lockdown and remote work, 64.4% people noticed changes in eating behaviors: of which 44.0% people eat more than before lockdown, while 20.0% eat less than before; 36.0% believe they did not notice a change regarding the amount of food consumed. Changes in eating behavior did not correlate with body weight (p = 0.37), but did correlate with changes in body weight (p = 0.00000). Body weight correlated with changes in body weight that occurred in the study group during lockdown (p = 0.000004). Individuals who restrict eating according to TFEQ 13 are more likely to report well-being (WHO-%), whereas individuals who are observed to lack control over eating and eat under emotional duress are more likely to report poor well-being (p = 0.000000). The study confirmed the change in dietary behavior and the occurrence of adverse health eating behaviors among remote and hybrid workers during the COVID-19 pandemic.